The link between logic, mathematics and imagination: evidence from children with developmental dyscalculia and mathematically gifted children. Issue 4 (19th March 2013) - Morsanyi, Kinga; Devine, Amy; Nobes, Alison; Szűcs, Dénes
Abstract: This study examined performance on transitive inference problems in children with developmental dyscalculia (DD), typically developing controls matched on IQ, working memory and reading skills, and in children with outstanding mathematical abilities. Whereas mainstream approaches currently consider DD as a domain‐specific deficit, we hypothesized that the development of mathematical skills is closely related to the development of logical abilities, a domain‐general skill. In particular, we expected a close link between mathematical skills and the ability to reason independently of one's beliefs. Our results showed that this was indeed the case, with children with DD performing more poorly than controls, and high maths ability children showing outstanding skills in logical reasoning about belief‐laden problems. Nevertheless, all groups performed poorly on structurally equivalent problems with belief‐neutral content. This is in line with suggestions that abstract reasoning skills (i.e. the ability to reason about content without real‐life referents) develops later than the ability to reason about belief‐inconsistent fantasy content.A video abstract of this article can be viewed at http://www.youtube.com/watch?v=90DWY3O4xx8 Abstract : The present study examined performance on transitive inference problems in children with developmental dyscalculia (DD), typically developing controls matched on IQ, working memory and reading skills, and in children with outstanding mathematical abilities. Whereas mainstream approaches currently consider DD as a domain‐specific deficit, we hypothesized that the development of mathematical skills is closely related to the development of logical abilities, a domain‐general skill. In particular, we expected a close link between mathematical skills and the ability to reason independently of one's beliefs.